Analysis of FDA's IQOS marketing authorisation and its policy impacts. Issue 4 (29th June 2020) - Lempert, Lauren Kass; Glantz, Stanton
Abstract : Background: Philip Morris Products SA (PMPSA) submitted a premarket tobacco application (PMTA) to US Food and Drug Administration (FDA) seeking an order permitting it to market IQOS in the USA. US law requires FDA to deny marketing authorisation if applicants fail to demonstrate that their product is 'appropriate for the protection of the public health'. FDA issued a marketing order for IQOS in April 2019, which Philip Morris is using to promote IQOS outside the USA. Methods: We analysed FDA's Technical Project Lead Review and marketing order for IQOS, relevant law and guidance on PMTAs and independent research on the health impacts of IQOS. Results: FDA found that the evidence PMPSA submitted did not demonstrate reduction in long-term disease risks and that IQOS aerosol emits toxins with carcinogenic and genotoxic potential, some at higher levels than conventional cigarettes. PMPSA did not appropriately consider the health impacts of dual use, the product's attractiveness to youth or data showing that consumers do not accurately perceive the addiction risks of IQOS. Despite FDA's own scientists' recommendations and independent research showing that IQOS presents serious risks to users including cytotoxic, genotoxic, hepatotoxic, cardiovascular and pulmonary risks, FDA concluded that IQOS is 'appropriate for the protection of the public health'. Conclusion: FDA's decision allowing IQOS to be marketed in the USA disregarded valid scientific evidence and misapplied the public health standard mandated by law. This decision may have important health impacts, influence marketing IQOS outside the USA and erode public confidence in FDA's future PMTA decisions.